The Epistemological Structure of Islamic Education in the Suharto Era: A Postcolonial Perspective - Uuh Buchori; Ilzamudin Ma'mur; Agus Gunawan; Ahmad Bazari Syam (Intiqad: Jurnal Agama dan Pendidikan Islam, 2023)
Indonesia has become one of the largest Muslim countries in the world by paying attention to Islamic education in both concept and policy. The system of government change is inseparable from the history of post-colonialism, including during the Suharto era with fundamental policies towards Islamic education. The Basic Structure of Epistemology as a Design for Understanding Islamic Educational Knowledge This study aims to explain the basic structure of Islamic education in the era of Suharto's leadership as President of the Republic of Indonesia. The research uses qualitative methods with a literature review approach. The results show that the leadership of the Suharto era with postcolonialism as a direction or sign has a self-affirming ideology on Pancasila and avoids forms of colonialism. The basic epistemology is the essential determination of the system or policy implemented by considering the expected form and purpose. In education policy, political orientation was emphasised. The basic instrumentation of Islamic education was identified with emphasis on the importance of Islamic religious education, which was included from elementary to tertiary level. The research implication is that the better the foundations of Islamic education, the better the understanding of the objectives of Islamic education through the curriculum.